ChemInform Abstract: A Rapid Approach for the Copper, Amine, and Ligand‐Free Sonogashira Coupling of 4‐Methyl‐7‐nonafluorobutylsulfonyloxy Coumarins under Microwave Irradiation. Issue 38 (10th September 2014) - Joy, M. Nibin; Bodke, Yadav D.; Abdul Khader, K. K.; Sajith, Ayyiliyath M.
Abstract The key for success of the coupling of nonaflate (I) with alkynes is the use of hydrated Bu4NF as mild base and as solvating agent to suppress the competitive nonaflate hydrolysis.